Statistical modelling of electricity price in Singapore power market - Tan, Eugene Ye Wu. (2010)
In most financial-driven markets, statistical tools are often used in the study of price behaviour. Currently, various researches have been conducted in the analysis of the electricity price behaviour using technical and mathematical tools. In addition is the widely used statistical method which is solely based on the historical data. With the deregulation of the electricity market in Singapore, such analysis of the electricity price behaviour will be crucial for both the consumers and generating companies.